2020
DOI: 10.1007/s12471-020-01422-0
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in quality of life and angina pectoris: 1-year follow-up of patients with refractory angina pectoris and spinal cord stimulation

Abstract: Aims Spinal cord stimulation (SCS) is a treatment for patients with refractory angina pectoris (RAP) who remain symptomatic despite optimal medical therapy and without revascularisation options. Previous studies have shown that SCS improves the quality of life in this patient group and reduces the severity of the angina pectoris. The aim of this prospective, singlearm observational study is to show this effect in a single-centre cohort using a multidisciplinary team approach to the selection process, with a fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 18 publications
(31 reference statements)
0
12
0
Order By: Relevance
“…To our knowledge this study is the first to publish results regarding the efficacy and safety of SCS in patients with RAP with a follow-up period of more than one year [10] , [12] , [16] . Patients in our patient population are relatively young at the time of spinal cord stimulator implantation, 67.3 (±9.0) years.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…To our knowledge this study is the first to publish results regarding the efficacy and safety of SCS in patients with RAP with a follow-up period of more than one year [10] , [12] , [16] . Patients in our patient population are relatively young at the time of spinal cord stimulator implantation, 67.3 (±9.0) years.…”
Section: Discussionmentioning
confidence: 96%
“…The clinical endpoints show that 22.0% (n = 29) of patients with RAP and SCS had an ACS and 32.5% (n = 43) underwent revascularisation (24.2% due to progressive angina pectoris and 8.3% due to an ACS) during the follow-up period. Other studies with a shorter follow-up period, ranging from six up to twelve months, reported occurrence of an ACS in 7.4% up to 10.3%, and revascularisation ranged from 3.3% up to 11.5% during follow-up [9] , [10] , [12] , [23] . These numbers show that the occurrence of a cardiovascular event is to be expected.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…The patient will be asked to start walking on the treadmill, the pace and angle of the treadmill will be steadily increased until angina is provoked, then TENS is initiated. 47 , 58 Based on the patient response to the TENS test the possible outcomes are: (i) positive: the patient is eligible for SCS, (ii) dubious: trial of two weeks TENS, or (iii) negative: the patient is ineligible for SCS. In case of a dubious test outcome a second evaluation will take place after two weeks of ambulatory TENS which is either positive or negative.…”
Section: Current Practicementioning
confidence: 99%
“…Reported rates of adverse events are 1% in case of infections and 7.8% in case of device related problems, 76 with an additional study describing an adverse event rate of 2.3% after 1 year of follow-up. 58 An important factor in the risk of adverse events occurring is operator experience. It has been proven in device-related treatment modalities that the experience of the operator significantly impacts the rate of adverse events.…”
Section: Current Use Of Scsmentioning
confidence: 99%